The relationship between truncation and phosphorylation at the C-terminus of tau protein in the paired helical filaments of Alzheimer's disease - Flores-Rodríguez, Paola; Ontiveros-Torres, Miguel A.; Cárdenas-Aguayo, María C.; Luna-Arias, Juan P.; Meraz-Ríos, Marco A.; Viramontes-Pintos, Amparo; Harrington, Charles R.; Wischik, Claude M.; Mena, Raúl; Florán-Garduño, Benjamin; Luna-Muñoz, José (Frontiers in Neuroscience, 2015)
We previously demonstrated that, in the early stages of tau processing in Alzheimer’s disease, the N-terminal part of the molecule undergoes a characteristic cascade of phosphorylation and progressive misfolding of the proteins resulting in a structural conformation detected by Alz-50. In this immunohistochemical study of AD brain tissue, we have found that C-terminal truncation of tau at Asp-421 was an early event in tau aggregation and analyzed the relationship between phospho-dependent tau epitopes located at the C-terminus with truncation at Glu-391. The aim of this study was to determine whether C-terminal truncation may trigger events leading to the assembly of insoluble PHFs from soluble tau aggregates present in pre-tangle cells. Our findings suggest that there is a complex interaction between phosphorylated and truncated tau species. A model is presented here in which truncated tau protein represents an early neurotoxic species while phosphorylated tau species may provide a neuroprotective role in Alzheimer’s disease.